Investigating female consumers’ environmentally conscious apparel purchase behaviour through Stimulus-Organism-Response framework - Krstić, Jelena; Rajić, Tamara; Kostić-Stanković, Milica; Vlastelica, Tamara (Serbian Journal of Management, 2024)
Abstract The objective of the study is to examine the influential factors of female consumers’ environmentally conscious apparel purchase behaviour, in the context of an emerging European economy. The study builds upon Stimulus-Organism-Response (S-O-R) theoretical framework and proposes the moderating role of style orientation on the direct effects on purchase behaviour. Online questionnaire-based survey was performed to gather data, using convenience sampling framework. Hypothesized relationships were examined on a sample including 343 responses. Partial Least Squares Structural Equation Modeling (PLS-SEM), using SmartPLS4, was applied to examine proposed research framework. Results of the study point to green self-identity as more influential direct determinant of purchase behaviour, in comparison to green advertising, and the mediating role of green self-identity in the relationship between green advertising and environmentally conscious apparel purchase behaviour. The study revealed the moderating function of style orientation in the relation between green self-identity and purchase behaviour. Theoretical and practical implications of the study are discussed and limitations of the study, followed by future research directions to overcome the drawbacks of the present research, are noted. Keywords: green advertising, green self-identity, environmentally conscious apparel purchase behaviour, style orientation